Uji Jarak Tanam Terhadap Pertumbuhan dan Hasil Tanaman Terung(Solanum melongena L)pada SistemAgroforestri Tanaman Karet(Havea brasiliensis) - Elida Purnama; Hadi Pranoto; Ellok Dwi Sulichantini (Mulawarman University, 2019)
The research was conducted to1). Optimaly planting distances analysis of eggplant in rubber agroforestry systemand 2). The research was conducted from May to September 2016 at Bunga Jadi district, Muara Kaman sub district, districtof Kutai Kartanegara.This research used a Randomized Group Design with single factor. The factor are planting distances ofeggplant with five level and five repetitions, those are 50 cm x 60 cm (j1), 60 cm x 60 cm (j2), 60 cm x 70 cm (j3), 70 cm x 70cm (j4), 70 cm x 80 cm (j5). The results showed, the planting distances treatment were not significantly effect of height ofplant, the number of leaves, the number of teas the blooming age, the weight of the fruit on 15, 30, 45 days after planting.And then the significantly effect on planting distances (60 cm x 70 cm) and total product of eggplant is 9.21 Mg ha1 in theweight of the fresh fruit per plot or hectare. Optimal product with distance of 60 cm x 70 cmis 9.21 Mg ha1(total production).The average production of eggplant in rubber agroforestry sistem is 7.82 Mg ha1 for 4 harvesting.The value of coefisientcorrelation in analysis covariant of multiple regression, r = 0.3459, the value of corelation is 34.59%, its showed thecorrelation value between treatment and production is low.